Eksistensi dan Perluasan Asas Legalitas dalam Undang-Undang No. 1 Tahun 1946 dan Undang-Undang No. 1 Tahun 2023 - Dyajeng Ayu Musdalifah; Ali Masyhar; Cahya Wulandari (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The principle of legality is a fundamental concept in criminal law that ensures legal certainty by stipulating that an act can only be punished if it has been clearly regulated by law prior to its commission and is not applied retroactively. This principle protects individuals from arbitrary actions by law enforcement and serves as the main foundation for criminal law enforcement. However, its application must be balanced with attention to substantive justice through interpretations that are responsive to the social and cultural context of society. Thus, the principle of legality not only guarantees legal certainty but also allows room for balanced and dynamic justice, functioning as a bridge between legal certainty and justice within the criminal justice system.